A new method for motion synchronization among multivendor's programmable controllers. (October 2018) - Cavalaglio Camargo Molano, Jacopo; Lahrache, Achraf; Rubini, Riccardo; Cocconcelli, Marco
Abstract: This paper is aimed at increasing the number of possible architectures of distributed control systems by investigating and developing novel methods for the synchronization of axes between PLCs and iPCs of different vendors. In order to find a global solution to this problem, particular attention has been focused on programmable controllers that can manage axes by means of point-by-point control or motion instructions. Two synchronization algorithms have been developed and validated for real and virtual axes; they differ in computational load so that they can be used with programmable controllers having high or low computational performances.